2019
DOI: 10.1016/j.cub.2019.06.042
|View full text |Cite
|
Sign up to set email alerts
|

m5C Methylation Guides Systemic Transport of Messenger RNA over Graft Junctions in Plants

Abstract: Highlights d m 5 C methylation is highly enriched in transcripts moving from shoot to root d TCTP1 and HSC70.1 mRNAs are not graft mobile in RNA methylation-deficient mutants d TCTP1 is translated after transport in distinct root cells and affects root growth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
174
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(186 citation statements)
references
References 59 publications
(113 reference statements)
7
174
1
4
Order By: Relevance
“…(3) Differential RNA cleavage at modified versus unmodified nucleotides is used to identify modified sites based on the percentage of sequence read-throughs and stops at each nucleotide (Birkedal et al, 2015;Garcia-Campos et al, 2019;Zhang et al, 2019d). In addition to those three types of methods, direct RNA sequencing by Oxford Nanopore Technology (Garalde et al, 2018) has recently been used successfully to map N 6methyladenosine (m 6 A) sites based on systematic base-calling errors at modified sites (Liu et al, 2019;Parker et al, 2019;Yang et al, 2019). In general, methods in categories 2 and 3 produce modification maps with nucleotide resolution, while methods in category 1 produce intervals containing a modification.…”
Section: Seeing Mrna Modifications: High-throughput Sequencing Delivementioning
confidence: 99%
See 1 more Smart Citation
“…(3) Differential RNA cleavage at modified versus unmodified nucleotides is used to identify modified sites based on the percentage of sequence read-throughs and stops at each nucleotide (Birkedal et al, 2015;Garcia-Campos et al, 2019;Zhang et al, 2019d). In addition to those three types of methods, direct RNA sequencing by Oxford Nanopore Technology (Garalde et al, 2018) has recently been used successfully to map N 6methyladenosine (m 6 A) sites based on systematic base-calling errors at modified sites (Liu et al, 2019;Parker et al, 2019;Yang et al, 2019). In general, methods in categories 2 and 3 produce modification maps with nucleotide resolution, while methods in category 1 produce intervals containing a modification.…”
Section: Seeing Mrna Modifications: High-throughput Sequencing Delivementioning
confidence: 99%
“…In plants, there are now reports on mapping of three distinct covalent nucleotide modifications in the bodies of mRNA: m 6 A (Li et al, 2014c;Wan et al, 2015;Shen et al, 2016;Duan et al, 2017;Anderson et al, 2018;Miao et al, 2019;Parker et al, 2019), 5-methylcytidine (m 5 C; Cui et al, 2017;David et al, 2017;Yang et al, 2019), and pseudouridine (C; Sun et al, 2019). Other types of mRNA modifications, including C-U editing of mitochondrial and plastidial mRNAs (Shikanai, 2006), alternative 59-caps (Kiledjian, 2018;Wang et al, 2019), and untemplated addition of nucleotides to mRNA 39-ends (De Almeida et al, 2018), will not be covered here.…”
Section: Mrna Modifications Identified In Plants and Other Eukaryotesmentioning
confidence: 99%
“…Transcriptome-wide m 5 C maps at variable depth are by now available for several tissues and cell lines of human/mouse (Squires et al 2012;Hussain et al 2013b;Khoddami and Cairns 2013;Blanco et al 2016;Amort et al 2017;Legrand et al 2017;Yang et al 2017;Wei et al 2018;Chen et al 2019;Huang et al 2019;Sun et al 2019), zebrafish (Yang et al 2019b), plant (Cui et al 2017;David et al 2017;Yang et al 2019a), archaeal (Edelheit et al 2013) and even viral (Courtney et al 2019a;Courtney et al 2019b) origin, persistently identifying sites with biased distribution in mRNAs and/or ncRNAs, reviewed in (Trixl and Lusser 2019). Several studies have further suggested regulatory roles for m 5 C in mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was shown in the context of leukemia that m 5 C in nascent RNA mediates formation of specific active chromatin structures (Cheng et al 2018). m 5 C can also guide systemic mRNA transport in plants (Yang et al 2019a), promote nuclear export of mammalian mRNA in conjunction with ALYREF (Yang et al 2017) and enhance mammalian and zebrafish mRNA stability facilitated by YBX1 Yang et al 2019b). Further, a negative correlation was noted between translation of mammalian mRNAs and the presence of m 5 C sites transcriptome-wide (Huang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also revealed that mobile RNA transcripts are enriched in the modified base 5-methylcytosine (m 5 C), indicating a role of RNA cytosine methylation in systemic RNA movement (Yang et al 2019). In plants, tRNA and mRNA m 5 C methylation is mediated by the methyltransferases DNMT2 and TRM4B (Burgess et al 2015; Cui et al 2017; David et al 2017) and loss of these enzymes was demonstrated to impair transcript mobility (Yang et al 2019). Future studies will need to be undertaken to determine if the dicistronic tRNAs identified in this study also confer mRNA mobility and to assess the role of cytosine methylation in mRNA transport in grapevine.…”
Section: Discussionmentioning
confidence: 99%